2008
DOI: 10.1016/j.tsf.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous solution–gel preparation of ultrathin ZrO2 films for gate dielectric application

Abstract: Zirconia ultrathin films were deposited by aqueous chemical solution deposition, using citratoperoxo-Zr(IV) precursors with different citric acid content. The precursor synthesis, thermal decomposition and crystallization of oxide powders was studied. This showed an effect of the citric acid content in every stage. The precursors were applied for the deposition of uniform, ultrathin films (< 30 nm thickness) as well. Tetragonal ZrO 2 crystallized starting from 500°C for thin films with a thickness of 10 nm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Moreover, in recent years, zirconia-based materials, including ZrO 2 -SiO 2 , have been proposed as a promising high-gate dielectric material for metal-oxide-semiconductor ͑MOS͒ transistors. [1][2][3] Thin films of ZrO 2 can be prepared by a range of methods, including physical vapor deposition, 4 chemical vapor deposition, 5 atomic layer deposition, 6 chemical solution deposition, 3,7 and anodizing. 8,9 Anodizing is the most simple and easiest method to form dielectric oxides, and this has been extensively used to form dielectric oxide films on aluminum and tantalum for electrolytic capacitor applications.…”
mentioning
confidence: 99%
“…Moreover, in recent years, zirconia-based materials, including ZrO 2 -SiO 2 , have been proposed as a promising high-gate dielectric material for metal-oxide-semiconductor ͑MOS͒ transistors. [1][2][3] Thin films of ZrO 2 can be prepared by a range of methods, including physical vapor deposition, 4 chemical vapor deposition, 5 atomic layer deposition, 6 chemical solution deposition, 3,7 and anodizing. 8,9 Anodizing is the most simple and easiest method to form dielectric oxides, and this has been extensively used to form dielectric oxide films on aluminum and tantalum for electrolytic capacitor applications.…”
mentioning
confidence: 99%
“…Polymorphic ZrO 2 possesses three different crystal structures at atmospheric pressure: monoclinic, tetragonal (t-), and cubic (c-), which are stable in the bulk form below *1170°C, between 1170 and 2370°C, and above *2370°C, respectively [6], and the mechanical, electrical, and catalytic properties are dependent on the crystal structures [7,8]. Particularly, stabilization of the high-temperature t-and c-phases at room temperature has been of significant interest for engineering applications and has generally been achieved by modulating the film thickness or particle/crystallite size [9,10] or by substituting Zr 4? with divalent or trivalent elements, such as Mg 2?…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the advantages of using aqueous chemical solution deposition for the fabrication and screening of ultrathin dielectric oxide films have been reported 16,17 . It was shown that the k values obtained from CSD films were equal to those for other deposition techniques, such as atomic layer deposition, which supports the use of this deposition technique for high k films.…”
Section: Introductionmentioning
confidence: 99%